Intermittent subclavian vein obstruction - Valls, Alberto (Cirugía del Uruguay, 1973)
The author presents a case of intermitent obstruction of subclavian vein and analyzes anatomical factors that trigger it. The anterior scalenous muscle is of importance and the disease should be treated by its resection. Radiological documentation is included.